Effect of amiloride and saline on nasal mucociliary clearance and potential difference in cystic fibrosis and normal subjects. - Middleton, P. G. (1993)
BACKGROUND--Mucociliary clearance is an important component of pulmonary defence. Maximum clearance is thought to depend on an optimal depth of the sol layer, allowing the most efficient interaction between the cilia and the overlying mucus layer. Sodium absorption, the major ion transport in human airways, is thought to be important in the regulation of the depth of the sol layer. In the airways of patients with cystic fibrosis sodium absorption is increased and mucociliary clearance decreased. Amiloride, a sodium channel blocker, has been shown to improve pulmonary mucociliary clearance in patients with cystic fibrosis. However, its effects on nasal mucociliary clearance in either normal subjects or those with cystic fibrosis are unknown. A study was therefore performed to investigate whether nebulised amiloride improves nasal mucociliary clearance in normal or cystic fibrosis subjects. METHODS--Nasal mucociliary clearance was measured by the saccharin clearance technique in 12 normal subjects and 12 with cystic fibrosis. For the control study measurements were made on two consecutive days and the mean time for each subject averaged. For the drug study measurements were also made on two consecutive days, after administration of nasally nebulised amiloride or placebo (saline) in a double blind manner. Nasal potential difference was measured in eight patients with cystic fibrosis after the administration of amiloride or placebo to assess the efficacy of deposition and duration of action. RESULTS--Baseline values of mucociliary clearance were significantly faster in the normal subjects than in those with cystic fibrosis. In both groups mucociliary clearance was increased after both saline and amiloride, with no significant difference between either treatment. As previously reported, baseline nasal potential difference was significantly more negative in the subjects with cystic fibrosis. Amiloride significantly reduced the potential difference for at least 60 minutes in these subjects. CONCLUSIONS--Nebulised saline significantly improves nasal mucociliary clearance in both normal subjects and those with cystic fibrosis. Amiloride did not appear to exert any additional effects in either group of subjects, despite evidence of its efficacy of deposition.